PENGARUH PENDAPATAN ASLI DAERAH,DANA ALOKASI UMUM, DAN BELANJA MODAL TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH (STUDI EMPIRIS PADA PEMERINTAH DAERAH KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2017-2019) - Eka Pradana Mahardika; Fauzan Fauzan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study has a purpose, namely to determine the effect of Regional Original Income, General Allocation Funds, and Capital Expenditures on the Level of Regional Financial Independence. The population in this study is PAD, DAU, Capital Expenditure and the Level of Regional Financial Independence in the Regency/City of Central Java Province in 2017-2019. The samples used in this study were 82 samples. The sampling method used purposive sampling technique. The statistical method uses multiple linear regression analysis model. The results of this study indicate that PAD and DAU have an effect on TKKD, while and DBH have no effect on TKKD.